Letter from C. P. Wornum to James Curtis Booth, May 25, 1853 - Wornum, C. P. (1853)
C.P. Wornum writes concerning a potential course of study with James Curtis Booth (1810-1888).
Keywords: Booth, James Curtis, 1810-1888; Chemistry teachers